A Survey of Parental Perception and Pattern of Action in Response to Influenza-like Illness in Their Children: Including Healthcare Use and Vaccination in Korea - Hwang, Ji Hyen (J Korean Med Sci, 2017)
Seasonal influenza is a significant cause of morbidity and mortality of children in Korea. However, few data are available on parental perception and action toward childhood influenza. This study aimed to characterize parental perception and patterns of action in response to influenza and influenza-like illnesses (ILIs), including vaccination and healthcare use. This prospective study involved a random survey of parents whose children were aged 6–59 months. The survey was conducted in October 2014. The study included 638 parents of 824 children younger than 6 years. Most parental information of influenza came from mass media (28.2%) and social media (15.5%). The factor that most often motivated parents to vaccinate their children against influenza was promotion of the government or mass media (36.6%). Negative predictors of immunization included safety concerns about influenza vaccination (28.1%) and mistrust in the vaccine's effectiveness (23.3%). Therefore, correct information about influenza and vaccination from mass media will be one of the cornerstones for implementing a successful childhood immunization program and reducing morbidity and mortality in Korea. Furthermore, to enroll younger children in vaccination programs, and to minimize coverage gaps, public concerns about vaccine safety should be resolved. The demographic data in the present study will be used to provide a deeper insight into a parental perception and will help health care providers increase influenza immunization rate.